1985
DOI: 10.1021/jf00065a048
|View full text |Cite
|
Sign up to set email alerts
|

UV-A photooxidation of .beta.-carotene in triton X-100 micelles by nitrodiphenyl ether herbicides

Abstract: Photooxidation of @-carotene in Triton X-100 micelles was stimulated by lipophilic nitrodiphenyl ether herbicides at concentrations as low as 5 pM after 15 min in UV radiation (UV-A between 315 and 400 nm). Bleaching of @-carotene by acifluorfen-methyl [methyl 5-[2-chloro-4-(trifluoromethyl)phenoxy]-2-nitrobenzoate) was proportional to UV-A intensity and independent of pH. White light (400-700 nm) alone was without effect. At pH 6.5, 100 pM acifluorfen [sodium 5-[2-chloro-4-(trifluoromethyl)phenoxy]-2-nitroben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There is evidence that N D PE herbicides can act as photosen sitizers in vitro, in the absence of photosynthetic m em branes, to enhance production of free radicals [26,27] and photooxidation of ß-carotene [27], How ever, in these systems the active wavelengths are apparently U V -A , not blue light. Furtherm ore, the photoreceptor is the herbicide, and its interaction with the carotenoid is destructive to the carotenoid.…”
Section: The Photoreceptor and Its Sitementioning
confidence: 99%
“…There is evidence that N D PE herbicides can act as photosen sitizers in vitro, in the absence of photosynthetic m em branes, to enhance production of free radicals [26,27] and photooxidation of ß-carotene [27], How ever, in these systems the active wavelengths are apparently U V -A , not blue light. Furtherm ore, the photoreceptor is the herbicide, and its interaction with the carotenoid is destructive to the carotenoid.…”
Section: The Photoreceptor and Its Sitementioning
confidence: 99%
“…The rate of radical production increases with pH and light, and retinal is a better photoreducing agent than p-carotene. Using these results and those of Orr and Hogan (1985), Lambert et al (1983), and Duke et a/. (1984), a mechanism for nitro biphenyl ether herbicides (scheme 1) which is analogous to the mechanism of action of nitroheterocyclic drugs (Rao et al, 1987;Moreno and Docampo, 1985) is proposed (Scheme 1).…”
Section: Discussionmentioning
confidence: 85%
“…Orr and Hess (1982) suggested a mechanism in which p- then reduces oxygen to produce superoxide radical. Later Hogan and Orr (Hogan and Orr, 1985;Orr and Hogan, 1985) proposed a slightly different mechanism in which the nitrobiphenyl ether herbicide is photoexcited and this excited molecule is reduced by p-carotene. Lambert et al (1983) and Duke et al (1984) have also suggested that the nitro radicals are involved in the herbicidal activity, although this is disputed (Ensminger et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The green and the red fluorescence of (all-E)-and ( 152)-pcarotene in KBr, induced by wavelength-selective pulsed laser radiation, have been recorded and explained.233 When (all-E)p-carotene, as a powder, was irradiated by X-rays at 77 K, in the dark, and then warmed, a vinyl-type radical was observed at --40 "C. Calculations suggested that this radical arose when a proton was lost from C-1 5.234 Photo-oxidation of p-carotene in micelles of Triton X-100 by ultraviolet-A light and nitrodiphenyl ether herbicides has been investigated. 235 The bleaching of canthaxanthin and of crocin [digentiobiosyl 83'diapocarotene-8,8'-dioate] (230) by photolytically produced alkoxyl radicals (which were derived from t-butyl hydroperoxide or from fatty acid hydroperoxides) has been studied and used to test antioxidants and radical scavengers. 236 In an investigation of its antioxidant activity, p-carotene slowed the autoxidation of phosphatidylcholine but not of t r i a c y l g l y ~e r o l s .…”
Section: S 9 Miscellaneous Physical Chemistrymentioning
confidence: 99%